2016
DOI: 10.1016/j.socscimed.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The feminine ideal and transactional sex: Navigating respectability and risk in Swaziland

Abstract: Women who engage in transactional sex are not only at increased risk of HIV and intimate partner violence, but also face social risks including gossip and ostracism. These social and physical risks may be dependent on both what a woman expects and needs from her partner and how her community perceives the relationship. Gender theory suggests that some of these social risks may hinge on whether or not a woman’s relationship threatens dominant masculinity. We conducted a qualitative study in Swaziland from Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
4
34
0
Order By: Relevance
“…4,5 These challenges include unplanned pregnancy, and HIV and other sexually transmitted infections (STIs). 5 Globally, adolescent girls and young women (AGYW) aged 15-24 years have HIV infection rates twice as high as their male counterparts [6][7][8] with estimates indicating that 31% of all new infections in sub-Saharan Africa are among AGYW. 6,7,9 Approximately 54.7% of Uganda's population are below 18 years of age with female youth twice as likely not to go to school as their male counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 These challenges include unplanned pregnancy, and HIV and other sexually transmitted infections (STIs). 5 Globally, adolescent girls and young women (AGYW) aged 15-24 years have HIV infection rates twice as high as their male counterparts [6][7][8] with estimates indicating that 31% of all new infections in sub-Saharan Africa are among AGYW. 6,7,9 Approximately 54.7% of Uganda's population are below 18 years of age with female youth twice as likely not to go to school as their male counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…18,22 Furthermore, transactional sex is also driven by normative expectations of courtship, which remain highly gendered. Men are expected to demonstrate their interest and investment in a relationship through material provision 8,18,22,29,[37][38][39][40] and women are expected to provide sexual access in exchange for material support. 6,8,9,27,29,37,40 There is a limited exploration in the literature of AGYW's views of the extent to which they feel coerced into entering transactional sex relationships or the role that any coercion has on their sexual health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study from South Africa found that while agency is likely an important mediator of risk for young women who engage in transactional relationships, complex pathways necessitate studies which carefully consider the nuances of how we conceptualize and measure transactional sex, as well as the social landscape within which these relationships exist [ 18 ]. The research presented here is part of a larger project that was designed to understand what women hope to gain materially and socially from transactional sex, how the social and material consequences of transactional sex may mediate the association between transactional sex and HIV risk, and whether or not a woman’s agency - in addition to simply the amount of material support she receives from her partner - is a key risk factor within sexual-economic relationships [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women’s sexual relationships affect their social status within a community and can generate material gains and losses beyond what they receive from their partner ( Figure 1 ) [ 5 , 21 , 22 ]. A high-status partner or access to consumer goods may increase a woman’s social capital within her community, particularly if the relationship is long term or they are married [ 6 , 7 , 20 , 23 ]. It can also strengthen her social network if she is able to provide for her family and friends through his financial support [ 4 , 5 , 7 , 10 , 20 ].…”
Section: Introductionmentioning
confidence: 99%